A synergy of liquid chromatography with high-resolution mass spectrometry and coagulation test for determination of direct oral anticoagulants for clinical and toxicological purposes - Maier, Vítězslav; Slavík, Luděk; Ondra, Peter (Biomedical chromatography, 2021)
Direct oral anticoagulants are an alternative to anticoagulants based on vitamin K antagonists. Monitoring of direct oral anticoagulant concentration levels is necessary in specific cases (e.g. in emergency conditions, for determination of the cause of bleeding, adverse effects, risk of drug-direct oral anticoagulants interaction); therefore, a sensitive and specific method is needed. A methanol protein precipitation method followed by liquid chromatography with high-resolution mass spectrometry was developed for simultaneous separation and determination of apixaban, betrixaban, edoxaban, dabigatran, rivaroxaban and ximelagatran. The proposed method was fully validated in terms of linearity, the limits of detection and quantification, intra- and inter-day trueness and precision, recovery, matrix effect, process efficiency and stability. The method shows a strong correlation (Pearson's correlation coefficients > 0.92) with coagulation assays of apixaban, dabigatran and rivaroxaban (dilute thrombin time for gatrans and anti Xa factor (anti-Xa) activity for xabans). In addition, the developed method was applied for the identification and determination of apixaban and dabigatran in post-mortem serum samples. The developed method is a good alternative to coagulation tests which may show various interferences.
Keywords: coagulation test; Administration, Oral; Chromatography, Liquid; Blood Coagulation Tests; liquid chromatography; vyšetření krevní srážlivosti; antikoagulancia; aplikace orální; high-resolution mass spectrometry; lineární modely; Mass Spectrometry; reprodukovatelnost výsledků; chromatografie kapalinová; Reproducibility of Results; direct oral anticoagulant; lidé; Anticoagulants; Humans; Sensitivity and Specificity; senzitivita a specificita; Linear Models; hmotnostní spektrometrie; toxicology